The impact of domestic violence on cognitive and psychological development of children: A scoping review - Rohman Hikmat; Ai Mardhiyah; Iyus Yosep (Jurnal Keperawatan Padjadjaran, 2022)
Background: Domestic violence is an incident that affects all family members, including children. The impact of domestic violence needs to be identified from the beginning, so that early treatment can be given. The purpose of this study was to describe the impact of domestic violence on child development. Purpose: The purpose of this study was to explore the coping strategies of adolescents with divorced parents.Methods: This study used the Scoping Review method. Literature were sourced from CINAHL, PubMed, and Scopus. The keywords are “domestic violence” AND “child” AND “impact”. The criteria for articles in this study are full text, free access, English language, and the publication period of the last 10 years (2013-2022). Results: Nine articles were found discussing the impact of domestic violence on children's development, namely the psychological impact, social impact, and the impact on school life. Several samples from UK ranged from 8-336 respondents. These impacts occur due to trauma events in children that are not treated immediately. The impact will be even worse if there is no immediate intervention to reduce the impact of domestic violence. Conclusions: Domestic violence can cause disturbances to the development of children including psychological impacts, social impacts, and impacts on school life.